2020
DOI: 10.1103/physrevb.102.035407
|View full text |Cite
|
Sign up to set email alerts
|

Revealing electromigration on dielectrics and metals through the step-bunching instability

Abstract: Electromigration, due to its technological and scientific significance, has been a subject of extensive studies for many years. We present evidence of electromigration in dielectric materials, namely C-plane sapphire, obtained from direct experimental observation of an atomic step-bunching instability driven by electromigration. We further expand upon our previously reported findings of electromigration induced step-bunching transformation of a metal surface. The only system where electromigration driven step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 101 publications
(229 reference statements)
0
2
0
Order By: Relevance
“…In this context, different materials are studied, such as CH 3 NH 3 PbI 3 , GaN, AlN, AlGaN, SiC, graphene, , PTCDA/Ag, W, , SrRuO 3 /(001) SrTiO 3 , KDP, Si, ferritin, diamond, and Al 2 O 3 . , The phenomenon of destabilization by both step-down (SD) and step-up (SU) direct currents of Si(111) vicinals was first observed by Latyshev et al on sublimating Si(111) surfaces and it was further shown based on the Burton–Cabrera–Frank (BCF) type of modeling that the directional asymmetry (bias) in the diffusion of the partially charged surface adatoms makes the motion of the steps from the vicinal surface unstable. The phenomenon of SB was investigated actively in the following years by experimental techniques as well as theoretically and numerically. …”
Section: Introductionmentioning
confidence: 99%
“…In this context, different materials are studied, such as CH 3 NH 3 PbI 3 , GaN, AlN, AlGaN, SiC, graphene, , PTCDA/Ag, W, , SrRuO 3 /(001) SrTiO 3 , KDP, Si, ferritin, diamond, and Al 2 O 3 . , The phenomenon of destabilization by both step-down (SD) and step-up (SU) direct currents of Si(111) vicinals was first observed by Latyshev et al on sublimating Si(111) surfaces and it was further shown based on the Burton–Cabrera–Frank (BCF) type of modeling that the directional asymmetry (bias) in the diffusion of the partially charged surface adatoms makes the motion of the steps from the vicinal surface unstable. The phenomenon of SB was investigated actively in the following years by experimental techniques as well as theoretically and numerically. …”
Section: Introductionmentioning
confidence: 99%
“…Step-bunching phenomenon has been extensively studied over the years by experimental techniques and by means of theoretical analyses and numerical simulations. Step-bunching instability has been observed in diverse crystalline materials, such as Si, ,, SiC, CH 3 NH 3 PbI 3 GaAs, GaN, , AlN, AlGaN, graphene, ,<...…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining environmentally friendly "green" materials for superhydrophobic coating plays a significant role and contributes to the improvement of the level and quality of life of the population [7][8][9][10]. Superhydrophobic sand on vicinal surfaces is an intriguing and innovative area of study that merges the principles of materials science and surface chemistry [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%